Improving Exp-Rule Scheduler For Real Time Services In LTE Downlink Networks - Udora N. Nwawelu , Cosmas I. Ani (International Journal of Advanced Science and Technology, 2020)
Popular Exponential Rule (Exp-Rule) scheduler is implemented in Long Term Evolution (LTE) network to increase the priority of real time (RT) services. Amidst good performance demonstrated by this scheme, it fails to satisfy the QoS requirements specified by third generation partnership project (3GPP) for RT services on video traffic packet loss ratio (PLR). In order to ameliorate this situation, this work proposed an improved Exp-Rule scheduler. The improvement incorporated a QoS priority weight factor into the Exp-Rule scheduling scheme. The proposed scheduler was tested on the basis of RT packet prioritization as specified by 3GPP to characterize different network services. This scheduler was evaluated and compared with the Exp-Rule scheduler using LTE simulator (LTE-Sim) on the basis of delay, PLR, throughput, and spectral efficiency network performance metrics; the proposed scheduler recorded a remarkable improvement over Exp-Rule scheduler in handling RT services.